2021
DOI: 10.3390/antibiotics10010094
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Broad-Spectrum Antibiotic Overuse across Diverse Hospital Contexts—A Qualitative Study of Prescribers in the UK, Sri Lanka and South Africa

Abstract: Antimicrobial stewardship programs focus on reducing overuse of broad-spectrum antibiotics (BSAs), primarily through interventions to change prescribing behavior. This study aims to identify multi-level influences on BSA overuse across diverse high and low income, and public and private, healthcare contexts. Semi-structured interviews were conducted with 46 prescribers from hospitals in the UK, Sri Lanka, and South Africa, including public and private providers. Interviews explored decision making about prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Given time constraints in general practice, pressures exist to minimise workload and this may contribute to patient prescriptions not being reviewed 8. Previous research provided evidence that limited time and cognitive resources may shape antibiotic treatment choices, with hospital doctors describing antibiotic prescribing as an ‘easy’ option, especially out of hours 14. Cognitive effort is likely to be even further reduced when choosing to continue a previous course of medication in general practice.…”
Section: The Psychology Of Repeat Prescriptionsmentioning
confidence: 99%
“…Given time constraints in general practice, pressures exist to minimise workload and this may contribute to patient prescriptions not being reviewed 8. Previous research provided evidence that limited time and cognitive resources may shape antibiotic treatment choices, with hospital doctors describing antibiotic prescribing as an ‘easy’ option, especially out of hours 14. Cognitive effort is likely to be even further reduced when choosing to continue a previous course of medication in general practice.…”
Section: The Psychology Of Repeat Prescriptionsmentioning
confidence: 99%
“… 66 The use of broad-spectrum antibiotics, in contravention to stewardship messaging, offered Sri Lankan hospital clinicians a partial response to missing infrastructures and patient poverty that can only be addressed with huge investment and extensive regulatory and policy interventions. 67 An ethnographic study conducted in Bangladeshi public hospitals found adherence to antibiotic use guidelines for diarrhoea patients was hampered by overcrowding, understaffing and lacking hygiene and sanitation. 68 In Ghana, a mixed-methods study identified how ‘inappropriate’ antibiotic use was driven by out-of-pocket payments, limiting patients’ contact with the formal health system and the unaffordability of complete antibiotic courses.…”
Section: Structuresmentioning
confidence: 99%
“…Similarly, in the healthrelated context of AMR, the diverse range of decision makers includes different types of doctors, patients, healthcare institutions and pharmaceutical companies. Additionally, these decision makers will be influenced by their respective national contexts and healthcare systems including differences between private and public healthcare (Tarrant et al, 2021). Given these various levels of impact, one solution is therefore to identify larger "superusers" (Quail et al, 2017), e.g., actors within the fossil-fuel or pharmaceutical industry, and ensuring they are held accountable for their imminently more significant actions.…”
Section: Decision Makersmentioning
confidence: 99%
“…Typically, any treatment decision is preceded by a sequence of choices, which form part of a longer decision making process. This, in turn, is further influenced by macro-and mezzo-level factors such as the state's healthcare policy, pharmaceutical distribution and health insurance systems (Tarrant et al, 2021). Initially, a general (binary) judgement about the existence of a bacterial infection has to be made.…”
Section: Strategiesmentioning
confidence: 99%